A melt inclusion study on volatile abundances in the lunar mantle. (15th March 2019) - Ni, Peng; Zhang, Youxue; Chen, Sha; Gagnon, Joel
Abstract: Earth's Moon was thought to be highly depleted in volatiles due to its formation by a giant impact. Over the last decade, however, evidence has been found in apatites, lunar volcanic glass beads, nominally anhydrous minerals and olivine-hosted melt inclusions, to support a relatively "wet" Moon. In particular, based on H2 O/Ce, F/Nd, and S/Dy ratios, recent melt inclusion (MI) work estimated volatile (H2 O, F, and S) abundances in lunar rocks to be similar to or slightly lower than the terrestrial depleted mantle. Uncertainties still occur, however, in whether the limited numbers of lunar samples studied are representative of the primitive lunar mantle, and whether the high H2 O/Ce ratio for pyroclastic sample 74220 is due to local heterogeneity. In this paper, we report major element, trace element, volatile, and transition metal data in MIs for 5 mare basalt samples (10020, 12040, 15016, 15647 and 74235) and a pyroclastic deposit (74220). With our new lunar MI data, H2 O/Ce ratios are still found to vary significantly among different lunar samples, from ∼50 for 74220, to ∼9 for 10020, ∼3 for 74235, 1.7 to 0.9 for 12008, 15016, and 15647, and 0.5 for 12040. H2 O/Ce ratios for these samples show positive correlation with their cooling rates, indicating a possible effect of post-eruptive loss of H on their H2 O/Ce variations. It is evident that most other lab and lunar processes, including loss of H2 O during homogenization, mantle partial melting, magma evolution, and ingassing during or post eruption are unlikely the causes of high H2 O/Ce variations among different lunar samples. By comparing ratios of F/Nd, S/Dy, Zn/Fe, Pb/Ce, Cs/Rb, Rb/Ba, Cl/K, Na/Sr, Ga/Lu, K/Ba, and Li/Yb between 74220 and other lunar samples, the possibility of 74220 originating from a volatile-enriched heterogeneity in the lunar mantle can also be excluded. With all the above considerations, we think that the H2 O/Ce ratio for 74220 best represents the pre-degassing lunar basaltic melt and primitive lunar mantle, either because it was formed by a rapid eruption process, or it was sourced from a deeper part of the lunar mantle that experienced less degassing H2 O loss during lunar magma ocean crystallization. With an H2 O/Ce ratio of ∼50, the primitive lunar mantle is estimated to contain ∼84 ppm H2 O. Comparing volatile abundances in melt inclusions, glassy embayments, and glass beads in 74220 yields the following volatility trend for volcanic eruptions on the lunar surface: H2 O ≫ Cl ≫ Zn ≈ Cu ≈ F > S ≈ Ga ≈ Cs > Rb ≈ Pb > Na > K ≈ Li. Using the melt inclusion data obtained thus far, the volatile depletion trend for the Moon from a MI perspective is estimated. Our results show that most of the volatile elements in the lunar mantle are depleted relative to the bulk silicate Earth by a factor of 2 to 20, however, a good correlation between half condensation temperature and the volatile depletion trend is not observed. The relatively flat pattern for the lunar volatile depletion trend requires a lunar formation model that can reconcile the abundances of these volatiles in the lunar mantle.